Understanding the Qur'an as a Cultural Product: A Study of Nasr Hamid Abu Zayd's Thought - Bimba Valid Fathony (Pelita: Jurnal Studi Islam Mahasiswa UII Dalwa, 2026)
Nasr Hamid Abu Zayd, an intellectual from Egypt, argued that the Quran is a 'cultural product' (muntaj thaqafi). This means that the text of the Quran was formed in reality and culture for more than 20 years. Historically, the text of the Quran does not appear in a vacuum. The text of the Quran contains all the cultural elements from which it was revealed. This study aims to delve deeper into Nasr Hamid Abu Zayd's thoughts regarding the view of "The Quran as a Cultural Product". The researcher will describe sub-discussions which include the biography of Nasr Hamid Abu Zayd, the text of the Quran in the perspective of Nasr Hamid Abu Zayd, two phases of the text of the Quran according to Nasr Hamid Abu Zayd, and the argument of the Quran as a cultural product from the perspective of Nasr Hamid Abu Zayd. In this study, the researcher used a qualitative approach method. This research is a library research, which is a research whose object of study uses library data in the form of books, journals, and articles as its data sources. The results of the research from the topic that the researcher raised are that "The Qur'an as a Cultural Product" does not mean the Qur'an as a human product that Nasr Hamid Abu Zayd meant from that view, namely the Qur'an as a cultural product because the Qur'an reflects the culture in which the Qur'an was revealed. This research enriches the study of the science of the Qur'an and contemporary interpretation, especially regarding Nasr Hamid Abu Zayd's thoughts on the concept of the Qur'an as a cultural product (muntaj tsaqāfī). This research attempts to explain that the concept is not intended to deny the origins of the Qur'anic revelation, but rather to explain the process of interaction of revelation with the social, linguistic, and cultural realities of Arabia during the time of revelation.